Monoclinic polymorph of 2-(pyrimidin-2-ylsulfan-yl)acetic acid - Silva, Manuela Ramos (2011)
The title compound, C(6)H(6)N(2)O(2)S, is a new polymorphic form of 2-(pyrimidin-2-ylsulfan-yl)acetic acid. Unlike the previous orthorhombic polymorph [Pan & Chen (2009 ▶) Acta Cryst. E65, o652], the mol-ecules are not planar: the aromatic ring makes an angle of 80.67 (17)° with the carboxyl plane. In the crystal, mol-ecules are linked by O-H⋯N hydrogen bonds into chains along [02].